Letter : Spanish Relief Fund - Elger, William
032-0019-001 Scottish Trades Union Congress General Council 33 ELMBANK CRESCENT GLASGOW, C.2. 1st April 1940. PHONE CENTRAL 3179 WILLIAM ELGER. J.P. SECRETARY Mr. H. V. Tewson, Assistant Secretary, Trades Union Congress, Transport House, London, S.W.1. Dear Mr. Tewson, SPANISH RELIEF FUND. I have to thank you for your letter of the 30th ultimo with receipt in regard to the above. On closing our Fund we have a balance of £1.9.4 - accumulated interest etc., and I am therefore enclosing a cheque for this amount which I shall be glad if you will add to our previous remittance. Your receipt per return will be appreciated. Yours truly, William Elger, Secretary. 292/946/32/19